2010
DOI: 10.1093/neuonc/noq084
|View full text |Cite
|
Sign up to set email alerts
|

Increases in the number of brain metastases detected at frame-fixed, thin-slice MRI for gamma knife surgery planning

Abstract: For gamma knife planning, 2.4-mm-slice MRIs are taken under rigid frame fixation, so tiny tumors become visible. This study evaluated differences in the numbers of brain metastases between conventional contrast-enhanced MRI (6 ± 1 mm slice thickness) taken before patient referral and contrast-enhanced MRI for gamma knife planning. The numbers of metastases on the 2 images were counted by at least 2 oncologists. For gamma knife planning, spoiled gradient-recalled echo images were obtained after 0.1 mmol/kg gado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…16 To optimize lesion conspicuity, gadobenate dimeglumine was selected for this study because it has been shown to have a higher contrast-to-noise ratio compared with other gadolinium-based agents. 24 Patients were examined using thin-section imaging (0.9-1.0-mm slice thickness, which increases the sensitivity of lesion detection 6,17 ), and isotropic imaging data are needed for SRS treatment planning for reliable morphological contouring.…”
Section: Discussionmentioning
confidence: 99%
“…16 To optimize lesion conspicuity, gadobenate dimeglumine was selected for this study because it has been shown to have a higher contrast-to-noise ratio compared with other gadolinium-based agents. 24 Patients were examined using thin-section imaging (0.9-1.0-mm slice thickness, which increases the sensitivity of lesion detection 6,17 ), and isotropic imaging data are needed for SRS treatment planning for reliable morphological contouring.…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы, локальный контроль оча-гов после радиохирургического лечения МГМ РП до-стигается в интервале 83-96 % [16,25]. Медиана ОВ больных с МГМ РП, сообщенная другими центрами, варьирует от 6 до 13 мес [8,10,11,15,18,19,21,26].…”
Section: Discussionunclassified
“…Additionally, other technical advantages such as new head coils with better signal-to-noise performance and also the parameters of the T1-weighted sequence might influence detectability of the benign enhancement. 3,19,25,38,39 However, confounding findings from early reactive enhancement may be limited if the imaging criteria of this enhancing pattern are considered. In our study, the types of enhancement shown on the first postoperative reactive MR scan could easily be attributed to reactive enhancement or residual gross tumor by comparing preand postsurgical scans, the latter revealing identical parts of the presurgical enhancing tumor.…”
Section: Discussionmentioning
confidence: 99%